The Role of Content Creators in the Profitability of Stores in Palu City - Alfiandi Patabang (Green Publisher Indonesia, 2026)
The digital era has transformed business operations, yet many MSMEs in mid-sized Indonesian cities struggle to leverage digital marketing effectively due to limited knowledge and resources. Content creator services have emerged as a potential solution, but empirical evidence on their financial impact remains scarce. This study analyzed the role of digital content creator services in improving MSME profitability in Palu City, Central Sulawesi. A qualitative case study approach was employed, using semi-structured in-depth interviews with five shop owners (cake shops, building materials stores, mobile phone shops) who had used content creator services for at least six months. Three main themes emerged: (1) Positive ROI all respondents achieved positive returns averaging 135%, with payback periods of less than one month; (2) Marketing cost control monthly marketing costs decreased by 22.2% (from IDR 1,850,000 to IDR 1,440,000) as traditional advertising was eliminated; (3) Operational efficiency promotional time reduced by over 70%, new customer acquisition increased by 180%. The combined effect produced an average net profit margin improvement of 6.3 percentage points (from 12.4% to 18.7%). Content creator services function as a high-yield, low-barrier digital transformation tool for MSMEs. Local governments should expand digital literacy programs, and content creators should offer performance-based pricing to reduce initial financial barriers for cost-sensitive MSMEs